2020
DOI: 10.3390/s20010255
|View full text |Cite
|
Sign up to set email alerts
|

CSRR-Based Microwave Sensor for Dielectric Materials Characterization Applied to Soil Water Content Determination

Abstract: A new and compact sensor based on the complementary split-ring resonator (CSRR) structure is proposed to characterize the relative permittivity of various dielectric materials, enabling the determination of soil water content (SWC). The proposed sensor consists of a circular microstrip patch antenna supporting a 3D-printed small cylindrical container made out of Acrylonitrile-Butadiene-Styrene (ABS) filament. The principle of operation is based on the shifting of two of the antenna resonant frequencies caused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 32 publications
(46 reference statements)
0
27
0
Order By: Relevance
“…[57] also developed an invasive open-ended microwave antenna which consisted of a 16 mm diameter by 170 mm long PVC sealed pipe containing a transmitting (TX) and a receiving (RX) dipole antenna, spaced 50 mm apart. Whist [58] reported that they had developed a compact, low cost and easy to manufacture narrowband open-ended antenna microwave sensor for measuring soil moisture.…”
Section: Invasive Open Ended Antenna (Radar) Microwavementioning
confidence: 99%
“…[57] also developed an invasive open-ended microwave antenna which consisted of a 16 mm diameter by 170 mm long PVC sealed pipe containing a transmitting (TX) and a receiving (RX) dipole antenna, spaced 50 mm apart. Whist [58] reported that they had developed a compact, low cost and easy to manufacture narrowband open-ended antenna microwave sensor for measuring soil moisture.…”
Section: Invasive Open Ended Antenna (Radar) Microwavementioning
confidence: 99%
“…A permittivity sensor based on a CSRR is presented in paper [ 74 ]. The intended application is the determination of soil water content.…”
Section: Brief Summary Of the Special Issue Papersmentioning
confidence: 99%
“…Microwave sensors based on complementary split‐ring resonators (CSRRs) have been reported in many different sensing situations, such as for magneto‐dielectric materials 6 soil water content, 7 complex permittivity, 8 conductive losses, 9 wireless pressure, 10 ethanol, 11,12 petrol, 13 oil, 14 strain level, 15 and surface cracks 16,17 . The CSRR structures were proposed for increased sensitivity and to reduce the size of the structure.…”
Section: Introductionmentioning
confidence: 99%